Kerentantan Hilirisasi Minyak Atsiri: Analisis Tematik Struktur Industri Parfum - Yohan Rayhan (Universitas Kristen Indonesia Toraja, 2026)
Indonesia is one of the world’s leading producers of essential oils; however, its industrial structure remains dominated by the export of raw materials, while value-added control in downstream sectors, particularly the domestic perfume industry, has not developed optimally. This study aims to analyze the structural vulnerabilities of essential oil downstreaming within the national perfume value chain and their strategic implications for strengthening domestic value-added capture. The research employs a descriptive qualitative approach through semi-structured interviews with five purposively selected key informants. Data were analyzed using NVivo software through open coding and thematic synthesis. The findings identify four major themes: imbalance in industrial structure and value chain, regulatory and governance fragmentation, upstream vulnerability and raw material sustainability, and global disruption alongside synthetic dominance. The results demonstrate that downstreaming challenges are structural and systemic, shaped by weak vertical integration, limited development of the midstream industry, and pressures from global technological and trade dynamics. The study concludes that strengthening downstreaming requires value chain restructuring, governance consolidation, development of essential oil derivatives and aromatic chemical industries, and the creation of a more stable investment climate to enhance competitiveness and domestic value-added control in the national perfume industry.